Characterization of Green Manure Sunn Hemp Crop Silage Prepared with Additives: Aerobic Instability, Nitrogen Value, and In Vitro Rumen Methane Production - Chatchai Kaewpila; Waroon Khota; Pongsatorn Gunun; Piyawit Kesorn; Thachawech Kimprasit; Chaweng Sarnklong; Anusorn Cherdthong (Fermentation, 2022)
Sunn hemp (SH, Crotalaria juncea, L.) is a tropical multiple-purpose legume. The green manure SH (GMSH) crop might display protein ecology in sustaining ruminants; however, its silage features remain unclear. To efficiently prepare GMSH crop silage, additive treatments consisting of control (no additive, CON), molasses (MO), Acremonium cellulase (AC), and Lactobacillus casei TH14 strain inoculant (TH14) were implemented using a completely randomized design. Repeated measurements were done after silage (AE conditions) in a small-scale silo system for 120 days and after aerobic instability (AE + AIS conditions). Briefly, ensiling loss and aerobic stability ranged from 150 to 175 g/kg and 8.3 to 104 days, respectively. In AE conditions, the pH ranged from 4.33 to 5.74, and MO or AC was desirable (p < 0.01) for lactic acid fermentation. AC reduced the fiber contents. MO increased soluble non-protein nitrogen by decreasing insoluble nitrogen. TH14 increased the ammonia nitrogen level and in vitro methane production. In AE + AIS conditions, AC led to more air damage to the chemical compositions and reduced digestibility in vitro. The results show that an optimization of additives could effectively modify GMSH crop silage to make it a good protein roughage source; however, more studies are required for effectively feeding ruminants.